HYDROLOGICAL PROPERTIES OF A MEDITERRANEAN SOIL BURNED WITH DIFFERENT FIRE INTENSITIES - González-Pelayo O.; Andreu V.; Campo J.; Gimeno-García E.; Rubio J.L. (My University, 2006)
The influence of vegetation cover on soil hydrological properties and its response to the impact of different fire intensities, in a Mediterranean forest environment, has been evaluated. The study was carried out in the Permanent Experimental Field Station of La Concordia (Llíria-Valencia, Spain), on a set of nine erosion plots (4 × 20 m2). The Station is located on a calcareous hillside S-SE oriented, with soils of Rendzic Leptosol type and supporting Mediterranean shrubland vegetation. All runoff generated and sediment produced in every rain event was collected from each plot. The set up includes a system of sensors for the continuous monitoring of climatic parameters (air temperature and humidity, rain volume, intensity, etc.). In June 1995, a set of experimental fires was carried out to the Station. Three of the plots were burned with high intensity fire, three with moderate intensity and the remaining were left unaltered. Soil water content and water retention capacity (WRC) were measured in the different plots and in two different vegetation covers: under canopy (UC) and in bare soil (BS). The pF curves were also obtained for each fire treatment. A year after the fires (June 1995-June 1996), great differences, reaching 77.15%, in runoff generation between fire treatments and the control plots were observed. No significant differences were detected on water retention capacity between soils UC and BS in the burned plots. However, these differences appeared in the control plots, giving UC and BS values of 13% and 18%, respectively. Plots corresponding to the high intensity fire treatment showed values of WRC significantly higher than those of the moderate intensity and of the control treatments. The pF curves show that the values of water volume, at the different pressure points studied, were slightly greater on UC soil. Values obtained for BS samples are higher in the fire treatments, showing significant differences in respect to the control plots at pF 1 and 2. These differences were also observed for UC soil, but in this case at pF 2, 2.5 and 4.2. © 2006 Elsevier B.V. All rights reserved.
Keywords: FOREST FIRES; MEDITERRANEAN ENVIRONMENT; PF; SOIL HYDROLOGY; WATER RETENTION CAPACITY